Development and performance testing of solar cookers - Kimambo, C.Z.M. (Journal of Energy in Southern Africa, 2007)
The most common type of energy used is firewood. In some Sub Saharan countries, up to 90% of total energy use is from firewood. The consumption of wood fuel is in some countries as high as twice the sustainable yield, something that has led to environ-mental degradation due to deforestation and scarci-ty of firewood. The use of fossil fuels such as kerosene and LPG for cooking is expensive. Solar energy is a non-consumptive and non-polluting fuel. It can help alleviate the problem of insecurity of cooking energy, which is the major domestic energy requirement. Several attempts have been made to introduce solar cookers in different coun-tries and have achieved variable successes. There are still critical issues yet to be resolved in order to make that technology acceptable for wider dissemi-nation. They include getting the most appropriate types of solar cookers for specific locations, opti-mum size/capacity, types of materials to be used, optimal design and affordable cost. In an attempt to resolve these issues, a comprehensive study involv-ing theoretical review, development work, experi-mental testing and evaluation of solar cookers was conducted for several years on six different types of solar cookers. The cookers are the ‘SunStove’ box cooker, wooden box cooker, panel cooker, reflector cooker with unpolished aluminium reflectors, reflec-tor cooker with polished aluminium reflectors and reflector cooker with glass mirror reflectors. This paper presents the results of the study. Results obtained indicate that many of the cookers could be used to cook food for households in areas with medium and high insolation, with appropriate selec-tion of the type and specification of the cookers. The specification should be based on the measured inso-lation data of the location indication of the direct and diffuse components. As a guiding tool, reflector cookers offer best comparative performance in areas with longest durations of clear sky (greatest direct beam), panel and collector cookers under moderate cloudy conditions and box cookers under very cloudy conditions.